Kinerja Keuangan dan Ukuran Perusahaan terhadap Return Saham dengan Kebijakan Deviden sebagai Variabel Intervening (Studi pada Perusahaan Manufaktur Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2015-2019) - Merizka Lovian; Sri Hermuningsih; Alfiatul Maulida (Ekonomis: Journal of Economics and Business, 2022)
This study was conducted to examine the leverage ratio as well as the benchmark for the company's stock returns with dividend regulations as an intervening variable for companies listed on the Indonesia Stock Exchange 2014-2019. This observation has a total sample of 57 samples using the purposive sampling method with a standard explaining dividend payments for 5 consecutive years. The first result is that the debt to equity ratio does not have a negative impact on stock returns, the second result is that the size of the company does not have a negative effect while the dividend payout ratio does not have a negative impact on stock returns. company size on stock returns. The conclusion of this observation is proven if there is no impact of dividend regulation in the correlation of financial performance on stock returns.